American Black-White Differences in Primary Tooth Crown Shape: The Crown Index - Edward F. Harris; Betsy D. Barcroft (Dental Anthropology Association, 2010)
The purpose of this tooth-size study was to compare the crown index-the ratio of buccolingal to mesiodistal crown size-in the primary teeth of contemporary American blacks and whites. Maximum MD and BL drown dimensions were obtained with sliding calipers from dental casts of children attending the graduate pedodontic and orthodontic clinics at the University of Tennessee, Memphis (n = 226). The crown index (BL/MD times 100) was calculated for all 10 tooth types (left and right sides were averaged prior to calculation). Only the maxillary first molar exhibited a significant sex difference (girls have a higher crown index). In contrast, 9 of the 10 tooth types have signficantly higher crown indices in blacks than whites. Analysis of the MD and BL crown diameters reveals that the race differencs are due exclusively to differences in mesiodistal crown lengths; the buccolingual crown breadths do not differ between these two races. Consequently, the crown indices are higher in blacks because of their larger MD dimensions. Differences in the indices conform to prior findings that American blacks have larger tooth crowns than whites in both the primary and permanent dentitions, and this study shows that the differences are due to the MD not the BL crown axis. Study of the crown components will shed light on how the crown shapes differ between these two races.